Development of a Prototype of Children's Literature E-Module Media Based on Google Workspace for Education to Improve Reading Literacy of Students in Elementary Schools - Imran , Muh Ali; Akhir, Muhammad; Arif , Tarman (FKIP - Universitas Riau, 2025)
This study aims to develop and describe a prototype of a children’s literature E-module utilizing Google Workspace for Education to improve reading literacy among fifth-grade elementary school students. The research employed a Research and Development (R&D) methodology using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation phases. The study involved 23 fifth-grade students from SD Inpres Mandalle. Data collection instruments included expert validation sheets, observation forms, and questionnaires to assess the module’s practicality and effectiveness. The findings reveal that: (1) the developed E-module prototype achieved high feasibility, with expert validation scores ranging from 93% to 95%; (2) its practicality was rated very good by both teachers and students, with scores of 97% to 98%; (3) its effectiveness was evidenced by a consistent increase in students’ reading literacy scores across sessions, rising from 63 in the first session to 84 in the third session; and (4) the module significantly enhanced students’ engagement, interest, and reading literacy skills. Overall, the study concludes that the children’s literature E-module based on Google Workspace for Education is a valid, highly feasible, practical, and effective instructional tool to support literacy development in elementary education.